2020
DOI: 10.3390/toxins12100657
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Genotypic and Phenotypic Characterization and Antibiotic Resistance Profile of Clostridium perfringens Type A and D Isolated from Feces of Sheep (Ovis aries) and Goats (Capra hircus) in Punjab, Pakistan

Abstract: Clostridium perfringens poses a serious threat to small ruminants by causing moderate to severe enterotoxaemia. Due to its ability to produce a wide arsenal of toxins, it is ranked among the most prevalent and important pathogens in livestock. This study focused on the molecular characterization of different Clostridium perfringens types along with their antimicrobial resistance profile. An overall higher prevalence of C. perfringens (46.1%) was detected based on mPCR among sheep and goats (healthy and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
5
12
0
4
Order By: Relevance
“…Neither type B nor C was found using specific primers when singlet and multiplex PCR was carried out. This is in agreement with previously reported type A and D toxinotypes isolated from sheep and goats from Punjab province of Pakistan (33). A previous study reported from Turkey has also shown only types A and D prevalent in sheep, examined by multiplex PCR; of these, 95% belonged to type A, and the remaining 5% were type D (51).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Neither type B nor C was found using specific primers when singlet and multiplex PCR was carried out. This is in agreement with previously reported type A and D toxinotypes isolated from sheep and goats from Punjab province of Pakistan (33). A previous study reported from Turkey has also shown only types A and D prevalent in sheep, examined by multiplex PCR; of these, 95% belonged to type A, and the remaining 5% were type D (51).…”
Section: Discussionsupporting
confidence: 93%
“…Preliminary clinical ailments, necropsy lesions, and histopathological findings are important and suitable tools, which help in disease diagnosis. Previously, a few epidemiological reports are available about the prevalence of enterotoxemia in goats (33). Therefore, this study describes the exact pathogenesis of enterotoxemia in goats and reports the types of C. perfringens toxins involved in the outbreak of this disease kept under desert conditions of Southern Punjab, Pakistan.…”
Section: Introductionmentioning
confidence: 97%
“…Morphologically identified characteristic colonies of C. perfringens on blood agar, perfringens agar, and egg yolk agar were confirmed biochemically through sugar fermentation reactions, gelatin liquefaction, and nitrate reduction tests. Pure colonies of C. perfringens fermented glucose, sucrose, maltose, and lactose, liquefied gelatin, and reduced nitrate while mannitol was found non-fermentative as reported earlier [ 29 ].…”
Section: Resultssupporting
confidence: 68%
“…There is much difference in the isolation rate of C. perfringens types across different regions, i.e., there are variations in the prevalence rates of C. perfringens [ 36 ]; likewise, type A is the predominant type in many countries including China, Pakistan etc. [ 29 , 30 , 31 , 37 , 38 ]. The high prevalence of alpha gene (type A) also signifies the importance of incorporating this toxinotype in vaccine strains along with type G and also suggests the use of an oil-based/montanide adjuvanted vaccine, rather than water-based alum precipitated vaccines, as proven successful in case of other clinically important diseases in Pakistan [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phát hiện C. difficile 25 g mỗi mẫu được đồng nhất trong 75 mL môi trường BHI (bổ sung 8 µg cefoxitin/mL, 250 µg cycloserine/mL và 0,1% taurocholate), trong 37°C/72h trong điều kiện kị khí. Dung dịch sau tăng sinh được cấy trên môi trường Chromagar agar C. difficile, các khuẩn lạc phát quang được xác định là C. difficile[5][6][7], khẳng định song song cùng kỹ thuật MALDI TOF[9].2.4.3. Xác định vi khuẩn C. perfringens và C. difficile mang gen sinh độc tốXác định vi khuẩn C. perfringens mang gen cpa bằng kỹ thuật PCR dựa trên độ dài đoạn gen khuếch đại.…”
unclassified